2016
DOI: 10.1016/j.xphs.2016.03.014
|View full text |Cite|
|
Sign up to set email alerts
|

Survival of the Fittest: Time-To-Event Modeling of Crystallization of Amorphous Poorly Soluble Drugs

Abstract: The objective of this study was to gain a quantitative understanding of the link between physicochemical properties and long-term and time-censored amorphous stability of poorly water-soluble drugs using parametric time-to-event modeling. Previously published data on amorphous stability and physicochemical properties of 25 structurally diverse neutral, poorly soluble compounds were used. To describe the general shape of the survival curve (probability of event at time >t), Constant, Gompertz, and Weibull hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The trends described by this research group have subsequently been confirmed by others. [4][5][6] For example, Mahlin and Bergstr€ om 6 reported that both molecular mobility (measured as the glass transition temperature) and configurational diversity (related to molecular weight) are important indicators of the crystallization propensity of pharmaceutical glasses.…”
Section: Current Knowledgementioning
confidence: 99%
“…The trends described by this research group have subsequently been confirmed by others. [4][5][6] For example, Mahlin and Bergstr€ om 6 reported that both molecular mobility (measured as the glass transition temperature) and configurational diversity (related to molecular weight) are important indicators of the crystallization propensity of pharmaceutical glasses.…”
Section: Current Knowledgementioning
confidence: 99%